2022
DOI: 10.7759/cureus.21404
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Acute Non-specific Back Pain Content on TikTok: An Exploratory Study

Abstract: In this study, we evaluated the scope of acute non-specific back pain (ANSBP) content available on TikTok (ByteDance Ltd, Beijing, China) in 2021. It is plausible that TikTok's popularity among teenagers, adolescents, and young adults may influence decision-making about what constitutes appropriate ANSBP self-care among a younger age cohort. MethodsWe examined 157 of the most viewed videos available through the hashtag #backpain available on TikTok in September 2021. We examined the following research question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…This study is based on methods of social media analysis developed by Zheluk, Anderson and Dineen Griffin for their analysis of TikTok low back pain content [30]. We adapted the methods to this study in the following ways.…”
Section: Methodsmentioning
confidence: 99%
“…This study is based on methods of social media analysis developed by Zheluk, Anderson and Dineen Griffin for their analysis of TikTok low back pain content [30]. We adapted the methods to this study in the following ways.…”
Section: Methodsmentioning
confidence: 99%
“…This study is based on methods of social media analysis developed by Zheluk, Anderson and Dineen-Griffin for their analysis of TikTok low back pain content [ 30 ]. We adapted their methods to this study in the following ways.…”
Section: Methodsmentioning
confidence: 99%
“…In their research, physician-created videos were in aggregate most closely concordant with scientific evidence. In another study, Zheluk and colleagues found chiropractors consistently produced TikToks with limited scientific content [ 30 ]. These limited scientific content chiropractic TikToks were consistently the most viewed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations